In the shadow of violence : politics, economics, and the problem of development - North, Douglass C. (Douglass Cecil); Wallis, John Joseph; Webb, Steven Benjamin, 1947-; Weingast, Barry R. (Cambridge : Cambridge University Press, 2013)
"This book applies the conceptual framework of Douglass C. North, Jo hn Joseph Wallis and Barry R. Weingast's Violence and Social Orders (Ca mbridge University Press, 2009) to nine developing countries. The cases show how political control of economic privileges is used to limit vio lence and coordinate coalitions of powerful organizations. Rather than castigating politicians and elites as simply corrupt, the case studies illustrate why development is so difficult to achieve in societies wher e the role of economic organizations is manipulated to provide politica l balance and stability. The volume develops the idea of limited-access social order as a dynamic social system in which violence is constantl y a threat and political and economic outcomes result from the need to control violence rather than promoting economic growth or political rig hts"--
Machine generated contents note: 1. Limited access orders: an introd uction to the conceptual framework / Douglass C. North, John Joseph Wal lis, Steven B. Webb and Barry R. Weingast; 2. Bangladesh: economic grow th in a vulnerable LAO / Mushtaq H. Khan; 3. Fragile states, elites, an d rents in the Democratic Republic of Congo (DRC) / Kai Kaiser and Step hanie Wolters; 4. Seeking the elusive developmental knife-edge: Zambia and Mozambique - a tale of two countries / Brian Levy; 5. Limited acces s orders: the Philippines / Gabriella R. Montinola; 6. India's vulnerab le maturity: experiences of Maharashtra and West Bengal / Pallavi Roy; 7. Entrenched insiders: limited access order in Mexico / Alberto Diaz-C ayeros; 8. From limited access to open access order in Chile, take two / Patricio Navia; 9. Transition from a limited access order to an open access order: the case of South Korea / Jong-Sung You; 10. Lessons: in the shadow of violence / Douglass North, John Wallis, Steven Webb and B arry Weingast.
Includes bibliographical references and index.
Keywords: Developing countries -- Economic conditions; Developing countries -- Social conditions